2020
DOI: 10.1038/s41586-020-2271-3
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic analysis of SARS-CoV-2 in two Wuhan hospitals

Abstract: Cite this article as: Liu, Y. et al. Aerodynamic analysis of SARS-CoV-2 in two Wuhan hospitals. Nature https://doi.The ongoing COVID-19 outbreak has spread rapidly on a global scale. While the transmission of SARS-CoV-2 via human respiratory droplets and direct contact is clear, the potential for aerosol transmission is poorly understood 1-3 . This study investigated the aerodynamic nature of SARS-CoV-2 by measuring viral RNA in aerosols in different areas of two Wuhan hospitals during the COVID-19 outbreak in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

74
1,668
7
52

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,756 publications
(1,864 citation statements)
references
References 14 publications
(13 reference statements)
74
1,668
7
52
Order By: Relevance
“…Another hospital study raises concerns for SARS-CoV-2 being transported as aerosols from droplet contaminated surfaces. This concern was based on measurement data associated with removing personal protective equipment, cleaning floors, and moving staff (Liu et al, 2020). The study also found SARS-CoV-2 in the air in outdoor areas at the hospital entrance and in front of a department store; the authors conclude it is possible that asymptomatic individuals in these areas may have contributed to these results.…”
Section: Supporting Evidence From Analytical Samples Of Sars-cov-2 Anmentioning
confidence: 92%
“…Another hospital study raises concerns for SARS-CoV-2 being transported as aerosols from droplet contaminated surfaces. This concern was based on measurement data associated with removing personal protective equipment, cleaning floors, and moving staff (Liu et al, 2020). The study also found SARS-CoV-2 in the air in outdoor areas at the hospital entrance and in front of a department store; the authors conclude it is possible that asymptomatic individuals in these areas may have contributed to these results.…”
Section: Supporting Evidence From Analytical Samples Of Sars-cov-2 Anmentioning
confidence: 92%
“…Here, we derive quantitative estimates for both the number and size of the droplets that remain airborne. Larger droplets, which are also abundant but associated with closeproximity direct virus transfer or fomite transmission (11), or which can become resuspended in air at a later point in time (12), are not considered here.…”
mentioning
confidence: 99%
“…Decontamination of equipment and the care environment must be performed after each patient and should be carried out as per practice protocols. Decontamination of all areas of the practice including the toilets can effectively limit the concentration of SARS-CoV-2 RNA in aerosols (Liu et al, 2020). It is generally advisable to avoid the use of fans that re-circulate the air.…”
Section: Protec Ti On: Hand Wa S Hing and Per Sonal Protec Tive Equmentioning
confidence: 99%